20 years of the Riester pension: Personal retirement provision requires reform - Johannes Geyer; Markus M. Grabka; Peter W. de Haan (DIW Weekly Report, 2021)
Introduced 20 years ago as a part of the 2001 pension reform, the Riester pension is meant to function as an essential component of the German pension system with the aim of compensating for decreasing public pensions. However, data collected by the SOEP show that this objective has not yet been achieved. For ten years, use of the Riester pension plan has been stagnating at around 25 percent of the working-age population, meaning the majority of households do not have a Riester contract. From a sociopolitical standpoint, the growing significant inequality in the use of the Riester pension is especially problematic. In 2020, only around 13 percent of individuals in the lowest income quintile had a Riester contract compared to almost 32 percent in the top quintile. Among pension recipients, the Riester pension has so far only played a minor role in securing their standard of living, accounting for just around five percent of their total retirement income. If the Riester pension is to function as an essential component of the German pension system, it must be fundamentally reformed. One reform possibility would be to organize personal pension provision via a mandatory pension fund, similar to the Swedish model of a standardized pension scheme product with low administrative costs. However, it must be guaranteed that low-income earners and the unemployed are able to pay the mandatory basic contributions.
Keywords: J32; H55; 330; Private retirement provision; Riester pension; SOEP